سید احمد خان كی فكر میں سیاسی جدیدیت: Political Modernity in the Thought of Sayyid Ahmad Khan - Dr Shahid Rasheed (Al Manhal Research Journal, 2023)
This paper aims to understand and analyiz Sayyid Ahmad Khan’s responses to the modern political institutions introduced by the British and political milieu of Nineteenth century colonial India. Sayyid Ahmad Khan was a keen observer and witeness of the end of the Mughal dynasty, East India Company’s rule, Indian Revolt of 1857, Muslim persecution after 1857, and the formal beginning of the British Raj. All these political upheavels and revolutions influenced Sayyid Ahmad Khan’s thought. He sought to understand the key to the British victory and the ground realities of India and Muslims of India. Sayyid Ahmad Khan, while agreeing with the tenets political modernity in the West, emphasises that the peculiar situtation of India must be considered for formulating any program of socio-political progress of India.